2006
DOI: 10.1002/ijc.21870
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different phases of an invitational screening program on breast cancer incidence

Abstract: The aim of this study was to quantify the effects of separate phases of an invitational screening program on breast cancer incidence at different ages. Our database included detailed municipality-specific information about invitations for mass-screening for breast cancer in 267 Finnish municipalities from time period 1987-2001. The age range was 50-74. For this study, the program was divided into 7 separate phases, and those that had not been invited served as a baseline. The incidence rate was modeled using P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…The APC-model including variables for the different phases of screening had a goodness of fit of 1.58 for invasive breast cancer and for invasive breast cancer plus DCIS, which indicates that not all variance in breast cancer incidence could be explained by the model. Besides, the RRs of our APC-model were on the higher end compared with estimated RRs of other studies using the same approach 6,24,30,31 and were indirectly assumed to be stable. Because new technologies, e.g., digital mammography, 26,32 change the sensitivity of the mammographic screening programme, this assumption is likely to fail.…”
Section: Discussionmentioning
confidence: 99%
“…The APC-model including variables for the different phases of screening had a goodness of fit of 1.58 for invasive breast cancer and for invasive breast cancer plus DCIS, which indicates that not all variance in breast cancer incidence could be explained by the model. Besides, the RRs of our APC-model were on the higher end compared with estimated RRs of other studies using the same approach 6,24,30,31 and were indirectly assumed to be stable. Because new technologies, e.g., digital mammography, 26,32 change the sensitivity of the mammographic screening programme, this assumption is likely to fail.…”
Section: Discussionmentioning
confidence: 99%
“…The recent decline was mostly attributed to a lower prevalence of hormone replacement therapy (HRT) use (Ravdin et al, 2007), whereas the levelling off of screening mammography rates in the late 1990s has been suggested as contributing (Glass et al, 2007). In relation to increased incidence in the 1990s, this is usually attributed to the introduction of mammographic screening (Jonsson et al, 2005;Seppänen et al, 2006). It is well established that this causes an immediate rise in incidence, mainly due to the early diagnosis of a many prevalent asymptomatic cancers (Jonsson et al, 2005;Svendsen et al, 2006).…”
mentioning
confidence: 99%
“…In the Netherlands, the stage II+ level was met , and a later report showed a clear decline in the rates of advanced cancers after the start of screening ). Recent studies from Finland, too, have reported a decrease in the post screening incidence of non-localised breast cancers (Seppanen et al 2006, Anttila et al 2008. Reduction in the rates of node positive tumours, tumours more than two centimetres in diameter, and stage II+ tumours in the screening era compared to those in the prescreening era have been reported in Sweden (SOSSEG 2007).…”
Section: Screening Performancementioning
confidence: 98%